Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2407-13-359
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and experimental studies regarding the expression and diagnostic value of carcinoembryonic antigen-related cell adhesion molecule 1 in non-small-cell lung cancer

Abstract: BackgroundCarcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is a multifunctional Ig-like cell adhesion molecule that has a wide range of biological functions. According to previous reports, serum CEACAM1 is dysregulated in different malignant tumours and associated with tumour progression. However, the serum CEACAM1 expression in non-small-cell lung carcinomas (NSCLC) is unclear. The different expression ratio of CEACAM1-S and CEACAM1-L isoform has seldom been investigated in NSCLC. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Unlike CEA and CEACAM6, CEACAM1 harbors a transmembrane domain and has alternative splicing variants. The expression ratio of the CEACAM1 long (CEACAM1-L) and short (CEACAM1-S) isoform is related with tumorigenesis [3942]. …”
Section: Ceamentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike CEA and CEACAM6, CEACAM1 harbors a transmembrane domain and has alternative splicing variants. The expression ratio of the CEACAM1 long (CEACAM1-L) and short (CEACAM1-S) isoform is related with tumorigenesis [3942]. …”
Section: Ceamentioning
confidence: 99%
“…Elevations of serum CEA of 50–60% can occur [50, 51]. CEACAM1, CEACAM6, and NCA-90 are also used prognostically to predict tumor recurrence of breast, lung, and colorectal cancers [42, 5255]. …”
Section: Ceamentioning
confidence: 99%
“…A separate study found CEACAM-1 expression in 81.3% of primary tumors from NSCLC patients with preserved expression in lymph node and hematogenous metastases which was negatively correlated with overall and progression-free survival (34). An association between NSCLC and serum CEACAM-1 levels has been reported recently (35). To the best of our knowledge, the current study is the first to report such an association regarding urine CEACAM-1 levels.…”
Section: Discussionmentioning
confidence: 77%
“…CEACAM1-L is the predominant expression form in normal lung tissues [60], while CEACAM1-S is predominantly expressed in most of NSCLC tissues associated with the incidence of NSCLC, especially S-isoform. Ratios of CEACAM1-S and CEACAM1-L were higher in NSCLC [61], indicating that CEACAM1-L and CEACAM1-S may participate in lung tumorigenesis, as explained in Fig. 6.…”
Section: Roles Of Ceacam1 In Lung Cancermentioning
confidence: 73%
“…Subsequently, SHP-1 is recruited to dephosphorylation of the p85α-binding motif of TLR2, which abrogates formation of the p85α-TLR2 signaling complex. This leads to suppress TLR2-dependent activation of the PI3K-Akt pathway, which reduces NF-кB-dependent antibacterial responses of pulmonary epithelial cells NSCLC [61], as a key factor for the early detection lung cancer and a potential therapeutic target for NSCLC.…”
Section: Roles Of Ceacam1 In Lung Cancermentioning
confidence: 99%